Strengthening Human Rights Protection in Nigeria: Safeguards Under the Police Act 2020 - Ugochukwu Godspower Ehirim; Morrison Ossai; Patrick Chukwunonso Aloamaka; Nwanneka Flora Ehirim (Khazanah Hukum, 2024)
The concept of Human Rights has become a critical factor in the definition of modern civilisation and constitutional democracies in the twenty-first century. The activities of the police remain central to the perception of human rights under municipal and international law according to the policies of the state-party. This article sets out to examine the provisions of the ‘new’ Police Force (Establishment) Act 2020 with a view to identifying the safeguards put in place by the law for strengthening the promotion and protection of human rights in Nigeria. It identifies factors which have contributed to inefficient policing and ever-increasing cases of human rights violations by the police and recommends sticking with the extant legal reforms for a better Nigeria Police Force. The Act introduces provisions such as mandatory accountability mechanism, abolition of use of force or torture to obtain statements from suspects as well as the requirement for the presence of a legal practitioners during a suspect’s interrogation, among others. The doctrinal research method is adopted in analysing statutory provisions and judicial precedents to assess the alignment of policing procedures with constitutional guarantees in line with global best practices. It is observed that despite the wide discretion afforded the Nigeria Police in the discharge of their duties which should boost the observance of human rights, the police abuse these discretions with the end result of serious violations of citizens’ rights which are guaranteed under the constitution. The article concludes that fostering a human-rights-based approach in the discharge of police duties alongside a stringent enforcement of the Police Act 2020 is imperative to sustaining lasting, far-reaching reforms.